Local and spa fee on the example of Kujawsko-pomorskie municipalities - Robert Kwaśniewski; Iwona Majewska (Prawo Budżetowe Państwa i Samorządu)
The article discusses facultative public levies in the Polish tax system – ie. local and spa tax. This publication presents legal structure of both taxes in accordance with the regulations of local taxes and fees contained in the Act of 12 January 1991. It also presents the results of empirical researches that have been carried out in Kujawsko-pomorskie municipalities, where local and spa taxes occured. The basic aim of study was to determine in which municipalities these fees were in force in 2010–2014 and what income had the individual municipal governments. Completed research would answer the question, whether the analysed charges are effective from local government`s point of view. The article is based on the analysis of legal acts, available literature and using case law of administrative courts. Furthermore, the authors presented the results of empirical research taken from Ms. Iwona Majewska thesis.